OC-046 Do Patients With A Previous Normal Colonoscopy Within The United Kingdom Bowel Cancer Screening Program Who Subsequently Have A Positive Fobt Require Repeat Colonoscopy?. (9th June 2014) - Sehgal, V; Stein, J; Bloom, S; Vega, R; McCartney, S; Obichere, A; Besherdas, K
Abstract : Introduction: Patients within the UK Bowel Cancer Screening Programme (BCSP) who have a normal colonoscopy are re-invited invited for Faecal Occult Blood test (FOBt) on a 2-yearly interval. If FOBt is positive, they are invited to have a repeat colonoscopy. The general polyp 'miss rate' is up to 22% in colonoscopy. Factors contributing to this include poor bowel preparation, rapid withdrawal time and endoscopist inexperience. However, endoscopists within the BCSP are highly skilled and selected following a rigid assessment process and poor bowel preparation is rare. Therefore, we hypothesised that patients who have previously had a normal colonoscopy within the BCSP who subsequently have a positive FOBt are unlikely to have a high-risk polyp or bowel cancer. Excluding these patients may avoid unnecessary invasive investigations and reduce the burden on an ever-stretching BCSP waiting list. We aimed to assess the detection of pathology in patients who have had a previous normal colonoscopy within the BCSP who subsequently have a positive FOBt and attend for repeat colonoscopy. Methods: Patients with a previous normal colonoscopy between 2007–2010 who re-attended within the BCSP for colonoscopy after repeat positive FOBt were identified from the UCLH 'in-house' BCSP database. The results of the colonoscopy and outcomes were then scrutinised. Results: A total of 1137 patients have had a normal colonoscopy to date within the BCSP and have subsequently been invited to have a repeat FOBt in 2 years time. From the patients who decided to participate in the second round of recruitment, 77 (6.7%) tested positive on FOBt and were invited for repeat colonoscopy. 8 declined another procedure. 6 patients (8%) had low risk adenomas (range 3–6 mm in size, 4 in right colon, 1 in sigmoid and 1 in left colon), all of who were discharged back to 2-yearly FOBt. 3 patients (4%) had hyperplastic polyps, 2 (3%) had inflammatory bowel disease and 58 (85%) had normal examinations. No patients had bowel cancer identified on repeat colonoscopy. Conclusion: No cases of bowel cancer were detected in FOBt positive patients who have previously undergone a normal colonoscopy within the BCSP. Only 8% of patients undergoing repeat colonoscopy had a low-risk adenoma detected mainly from the right colon. Discharging patients with a normal colonoscopy in the BCSP from further screening would reduce pressure on endoscopy screening units and any potential morbidity associated with the procedure. From this study, excluding such patients could have avoided 20 colonoscopy screening lists (approximately 80 procedures) over 3 years in our unit. If findings are similar in other centres, current national guidelines should be changed. Disclosure of Interest: None Declared.